PERAN FATWA DSN MUI DALAM PENYESUAIAN PRAKTIK AKAD MURABAHAH PADA BANK SYARIAH: PERSPEKTIF HUKUM EKONOMI ISLAM - Lubis, Rahmad; Nuranisah, Nuranisah; Purnama, Desi; Prawiro, Atmo (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
This study focuses on analyzing the role of the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI) in the application of the practice of murabahah contracts in operations in Islamic banks. This study uses library research, including DSN MUI fatwas, regulations, and studies related to operational procedures. Qualitative analysis aims to understand the role of fatwas in Islamic banking operations. The study found that DSN MUI has a strategic approach to providing legal guidance and legitimacy to Islamic banks, but there are challenges in its implementation, such as compliance with operational procedures and regulatory compliance. This study recommends an empirical study to evaluate the implementation of Islamic banking practices more closely.